Answer:
y + 5 = -
(x + 3)
Explanation:
The equation of a line in point- slope form is
y - b = m(x - a)
where m is the slope and (a, b) a point on the line.
y - 4 = 2(x - 6) is in this form with slope m = 2
Given a line with slope m then the slope of a line perpendicular to it is
= -
= -
![(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ybjkeso7qr5r7js5h0mv9de35dih0sxfpl.png)
Hence the equation passing through (- 3, - 5) is
y - (- 5) = -
(x - (- 3)), that is
y + 5 = -
(x + 3) ← equation of perpendicular line